MEDIEVAL CLIMATE WARMING AND ARIDITY AS INDICATED BY MULTIPROXY EVIDENCE FROM THE KOLA PENINSULA, RUSSIA - Kremenetski K.V.; MacDonald G.M.; Boettger T.; Vaschalova T.; Sulerzhitsky L.; Hiller A. (My University, 2004)
Data obtained from the low-elevation Khibiny Mountains (ca. 67–68°N; 33–34°E) on the Kola Peninsula, northwest Russia, indicate a period of exceptionally warm and dry conditions commenced at ca. AD 600 and was most pronounced between ca. AD 1000 and 1200. Warmer summer temperatures during this period (coeval with the ‘Medieval Warm Period’ observed in other parts of Europe) are evident in a 100–140 m upward shift in the pine (Pinus sylvestris L.) limit in the Khibiny Mountains. On average, the cellulose of pine trees that grew between ca. AD 1000 and 1300 is enriched by δ13C values of around 1‰ compared to the modern trees from the region, further suggesting warmer summer climate than at present. The Medieval Warm Period was also accompanied by a steady decline in avalanche activity and the resulting formation of soils on the current avalanche cones in the Khibiny Mountains, suggesting lower winter precipitation and thinner snow cover. Lower precipitation is also evident by currently submerged tree stumps dating to the medieval period that indicate lower lake levels on the Kola Peninsula. In the middle of the peninsula at about AD 1000, the level of small closed-basin lakes was ∼1 m lower than the modern time at some sites. Drier conditions may be attributable to decreased cyclonic activity. The medieval warm and dry episode was followed at ca. AD 1300 by the development of a colder climate with increased precipitation resulting in a decline in the alpine pine limits, increased avalanche activity, and higher lake levels. That phase corresponds to the modern aeolian episode reconstructed in subarctic Finland. Our results indicate that the Medieval Warm Period on the Kola Peninsula experienced notably warm and dry conditions. Hence, this period of warming extends to northwestern Russia as well as other parts of Europe.
Keywords: Medieval optimum; Buried soils; Isotope studies; Radiocarbon dating; Climate